Psychometric properties of the caregiver-teacher report form in a sample of Norwegian preschool children. (1st November 2022) - Stensen, Kenneth; Jozefiak, Thomas; Lydersen, Stian
Abstract: Purpose: The caregiver-teacher report form (C-TRF) is included in the Achenbach system of empirically based assessment (ASEBA) and widely used to measure child psychopathology. In Norway, the C-TRF is frequently used by the Educational and Psychological Counselling Service or for referrals to special health services, however, its psychometric properties in the Norwegian context have not yet been explored. The aim of this study was to investigate the internal consistency of the C-TRF and its factorial validity in a Norwegian preschool context. Method: This study is based on baseline data from the project Children in Central Norway, where a total of 169 preschool teachers reported on the C-TRF for 1430 children aged 1–6 years. Results: The findings indicate promising psychometric properties for the C-TRF in terms of internal consistency and factorial validity, however, the somatic complaints scale seems problematic because of its poor psychometric properties. Conclusion: Users of the C-TRF can be confident in the instrument's applicability in a Norwegian context, however, careful considerations when applying the somatic complaints scale in clinical decision making is warranted.